Impression Making and Lab Work Authorization Forms in Fixed Prosthodontics: A Preclinical Exercise - Tarek El-Kerdani; Arthur Nimmo (Association of American Medical Colleges, 2016)
Abstract Introduction Making a final impression using a custom tray for fixed prosthodontics is a widely accepted procedure that is taught in many dental schools. As such, achieving competency in impression making and lab communication is a new Commission on Dental Accreditation curriculum requirement for all dental schools in the US. Methods This resource presents an instructional slide show on the clinical steps required in fabricating a custom tray using a visible light-cured resin, making a successful impression, and writing a work authorization form for the fabrication of a fixed dental prosthesis. The presentation also contains a brief overview of alternative techniques and materials used as well as basic points for self-evaluation for the custom tray and the final impression. This activity was conducted as a small-group team-based learning exercise in a preclinical setting, where a self-assessment form was provided for students to evaluate their work. Results Examiners indicated that students who completed this exercise had a deeper understanding of the sequencing of steps involved in the construction of a fixed partial denture as well as better lab communication skills compared to students from previous classes who did not participate in the exercise. Discussion The preclinical setting provided students with a relaxed atmosphere for fabricating a custom tray using visible light-curing material. This exercise is part of a larger preclinical exercise that takes students through all the steps involved in the fabrication of a fixed dental prosthesis, from impression making to the evaluation of the framework made by the lab.